IPTEKS PENGELOLAAN RISIKO KEPATUHAN PADA PT. BANK SULUTGO - Rawis, Gracela Gloria; Sabijono, Harijanto (Universitas Sam Ratulangi, 2018)
In running a business, the company cannot be separated from the risks that can threaten the company. Risks that arise require attention and improvement so that a business can survive and compete in the business world. There are various kinds of risks that arise especially at banks, usually in the form of reputation, operational, credit, market, strategic, legal, liquidity and compliance risks. From these risks, Bank SulutGo feels the need to conduct monitoring and evaluation to minimize the existing risks. This journal aims to discuss compliance risk management implemented by SulutGo Bank. By using the implementation method based on OJK Regulation Number 18 / POJK.03 / 2016 on March 16, 2016. This regulation contains the implementation of risk management for commercial banks. Based on the methods available, several steps need to be applied. This journal raises four steps, namely: identifying, measuring, monitoring, and finally mitigating. These four steps need to be done to achieve risk management that is right on target.Keywords: risk management, compliance function, identification, measurement, monitoring, mitigation,